Mães e vacinação das crianças: estudo de representações sociais em serviço público de saúde Mothers and the vaccination of children: a study of social representations in the public health sector - Maria Vicencia Pugliesi; Luiz Fernando Rangel Tura; Maria de Fátima Siliansky de Andreazzi (Revista Brasileira de Saúde Materno Infantil, 2010)
OBJETIVOS: levantamento dos fatores envolvidos na significativa observância das mães ao calendário vacinal do Programa Nacional de Imunizações. MÉTODOS: amostra de 124 gestantes, divididas em dois grupos: 61 gestantes nulíparas e 63 multíparas, entre as que frequentaram o serviço de Ginecologia/ Obstetrícia e Pediatria do CMS Heitor Beltrão (Rio de Janeiro-RJ) no período de agosto de 2003 a janeiro de 2004. Para apreender os sentidos de vacinação, foram utilizados o teste de evocação "vacina" e um questionário. RESULTADOS: identificou-se que as mães associaram imunização essencialmente a "prevenção" e "proteção". As percepções "bom", "cuidado" e "responsabilidade" identificadas no sistema periférico da representação as impelem concretizar no cotidiano essas cognições adquiridas, garantindo o cumprimento do calendário vacinal. Tais sentidos relacionam-se estreitamente com o discurso da Epidemiologia que caracteriza as ações de imunização como ações de proteção específica. CONCLUSÕES: a experiência com vacinação de crianças no Brasil, com observância próxima a 90%, alcançada em pouco mais de duas décadas, indica que uma visão ativa e consciente dos benefícios das imunizações substituiu possíveis desconhecimentos ou resistências por parte das mães em relação à vacinação. Identificou-se que um conjunto específico de fatores políticos, econômicos, culturais, tecnológicos - nacionais e internacionais - estão envolvidos na oferta de imunobiológicos à rede de saúde brasileira e contextualizam a atual observância ao calendário vacinal. OBJECTIVES: a survey of the factors involved in significant observance on the part of mothers of the National Immunization Program's vaccination calendar. METHODS: a study of 124 pregnants divided into two groups: 61 nulliparous pregnant women and 63 multiparous women attending the Gynecology/ Obstetrics and Pediatrics service of the Heitor Beltrão CMS (Rio de Janeiro-RJ) in the period August 2003 to January 2004. In order to understand the meanings of the vaccination, a test of the ideas evoked by the word "vaccine" and a questionnaire were applied. RESULTS: it was identified that mothers associated immunization essentially with "prevention" and "protection". The ideas of "good", "careful" and "responsible" identified in the peripheral representations system led them to place these acquired cognitive concepts in the concrete context of their everyday lives, thereby ensuring that the vaccination calendar was observed. These feelings are strictly related to the epidemiological discourse that characterizes immunization as a specific act of protection. CONCLUSIONS: the Brazilian experience of child vaccination, with almost 90% observance achieved in little more than two decades, suggests that an active and informed point of view on the part of the beneficiaries of immunization has replaced any misunderstandings or resistance that mothers may have had with regard to vaccination. A specific set of political, economic, cultural and technological factors-both national and international-were identified as being involved in the provision of immunobiological services by the Brazilian health network and these are reflected in the present degree of observance of the vaccination calendar.